Science & Technology and Innovation Policies in Science & Technological Research, Development, and Implementation - Putera, Prakoso Bhairawa; Jannah, Lina Miftahul (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2013)
This article analyses the observation of science & technology (Iptek) and innovation policies in activities of science and technological research, development, and implementation. Science & technology and innovation policies become an important study subject since in some countries this field gives positive effect to competitiveness of a nation. Qualitative approach was selected in studying science & technology and innovation policy in Indonesia since its appropriation with the objective of portraying national policy in science & technology and innovation. Method employed was content analysis qualitative with framing analysis, which in this study refers to concept of science & technological research, development, and implementation. The results of this study shows that national policy of Indonesia during 2000-2011 period were less supportive to development, research, diffusion, and implementation of technology in regions, proven by evidence that there was only few policies supporting the system implementation of science & technological research, development, and implementation in Indonesia.